2020
DOI: 10.1080/02705060.2020.1770874
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of regional and local factors in shaping zooplankton diversity in high-altitude tropical shallow lakes

Abstract: In Brazil, although, high-altitude shallow lakes comprise large parts of conservation units and are considered highly important environments for biodiversity studies, little is known about the factors that regulate the zooplankton community. In the present study, we sought to identify the effect of regional (hydroperiod and altitude) and local (lake area and macrophyte cover) factors on the zooplankton communities in eight shallow high-altitude lakes (from 1080 m a.s.l. to lakes above 1200 m a.s.l.) in the Esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Overall zooplankton species distribution, diversity and abundance in the study sites are influenced by various environmental and biological factors such as water colour, surface area, depth and trophic level, predation, breeding and vertical migration [9][10][11]15,[16][17][18]. The results of this present study revealed that some common types of freshwater zooplankton are Cladocera, Copepoda, Protozoa, marine Tintinnida, Nemata, Rotifera; which forms the bulk of zooplankton groups in previous studies [2][3][4][13][14][15][16][17][30][31][32][33][34][35] and are in agreement with our present findings. The submissions of other researchers suggested that the availability of these zooplankton species could be as a result of genetic adaptation; coupled with other relevant environmental factors [3,4,36].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Overall zooplankton species distribution, diversity and abundance in the study sites are influenced by various environmental and biological factors such as water colour, surface area, depth and trophic level, predation, breeding and vertical migration [9][10][11]15,[16][17][18]. The results of this present study revealed that some common types of freshwater zooplankton are Cladocera, Copepoda, Protozoa, marine Tintinnida, Nemata, Rotifera; which forms the bulk of zooplankton groups in previous studies [2][3][4][13][14][15][16][17][30][31][32][33][34][35] and are in agreement with our present findings. The submissions of other researchers suggested that the availability of these zooplankton species could be as a result of genetic adaptation; coupled with other relevant environmental factors [3,4,36].…”
Section: Discussionmentioning
confidence: 60%
“…Human activities through industrialization, deforestation, farming, oil exploration and transportation have resulted in climate changes which adversely affect the distribution, assembly structure of aquatic communities, especially the composition, richness and species diversity [1][2][3]. Activities of humans also lead to discharge of untreated animal wastes like releases from sewage and septic tanks, run-off from farm lands, laundering waste into surrounding bodies of water.…”
Section: Introductionmentioning
confidence: 99%
“…Human activities play an essential role as a vector of new introductions of M. macrocopa —one of the most commonly used cladoceran in standardized laboratory bioassays worldwide (Martínez-Tabche et al, 2000 ; Iannacone & Alvariño, 2002 ; Nandini et al, 2004 ). Following its previous introduction in South America, e.g., in Peru (Valdivia-Villar, 1988 ), Argentina (Paggi, 1997 ), and Chile (Iannacone & Alvariño, 2002 ), this vector is a probable source for its late appearance in Brazil (Elmoor-Loureiro et al, 2010 ; Rietzler et al, 2014 ; Eskinazi-Sant’Anna et al, 2020 ). Hence, as dispersal may not limit its spread in invaded areas, bottleneck and/or biotic resistance are more likely to be the most critical factors determining this high unfilling.…”
Section: Discussionmentioning
confidence: 99%
“…They supply necessary amount of protein, lipid, essential amino acids and fatty acids, ~ 49 ~ which provide immune stimulation, pigment enhancement, physiological regulations, and growth and quality larval production (Mayzaud et al, 2016;Manickam et al, 2017) [44,45] . Zooplanktons are highly sensitive to detect any environmental disturbances through changes in species composition, abundance, and body size, distribution and diversification (Xiong et al, 2020; Eskinazi-Sant'Anna et al, 2020) [46,47] . Zooplankton species composition in a particular water body is controlled by several ecological factors, including nutritional load and pollution status (Bhavan et al, 2015a) [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Ostracods are found in heavily polluted water and they serve as indicator species of climate and ecosystem changes (Martens et al, 2008) [7] . It has been reported that Heterocypris incongruens, Candona neglecta, Prionocypris zenkeri, Ilyocypris bradyi, Cypridopsis vidua, Vestalenula boteai, Hemicypris inversus, Hemicypris congenera, Cypretta hirsute, Trajancypris clavata and Cypretta hirsuta were suggested as indicators of organic pollution in Tibetan Plateau surrounded by the Himalayas and high-altitude shallow lakes in Brazil (Kulkoyluoglu et al, 2016; Eskinazi-Sant'Anna et al, 2020) [54,47] . Here, the occurrences of such ostracoda species (Heterocypris incongruens, Prionocypris sp., Candona sp., and Cypretta sp.)…”
Section: Discussionmentioning
confidence: 99%